Barking mad? Another lunatic hypothesis bites the dust. Issue 7276 (23rd December 2000) - Chapman, Simon; Morrell, Stephen
Abstract: Objective: To assess whether dog bites requiring hospital admission occur more at the full moon. Design: Review of dates of admission for dog bites to accident and emergency departments, June 1997 to June 1998, compared with dates of the full moon. Setting: All public hospitals in Australia. Main outcome measures: Admissions for dog bites. Results: 12 peak clusters of admissions were unrelated to the time of the full moon. Conclusion: Dog bites are no more frequent on full moons than at any other time of the month. Sceptics rejoice.